Fatigue pada Pasien Gagal Jantung - Bambang Aditya Nugraha (STIKes Karsa Husada Garut, 2016)
Heart faillure is an illness that caused physical and psychological problem. Physical problem such as activity intolerant, ineffective breathing patern etc. Psychological problem related to Heart faillure is depression, anxiety and chronic stress. Fatigue is combination physical and psychological problem in heart faillure patient. Fatigue is decreased physical and psychological capacity. Fatigue in heart faillure is severe physical and psychological disability that not perished when managed with rest and caused discomfort. Fatigue is happened by compensatory mechanism and neurohormonal changes. Related factors to fatigue is physical, psychological and environmental. Neurohormonal changes and mediator activity is physical factor. Depression, anxiety and chronic stress is psychological factor. Family support is environmental factor. Tools to measure fatigue level is Functional Assessment of Chronic Illness Therapy (FACIT) and Piper Fatigue Scale (PFS). The tools is possibl to use in other chronic illness such as terminal renal faillure.